Characterization of autonomic symptom burden in long COVID: A global survey of 2,314 adults - Larsen, Nicholas W.; Stiles, Lauren E.; Shaik, Ruba; Schneider, Logan; Muppidi, Srikanth; Tsui, Cheuk To; Geng, Linda N.; Bonilla, Hector; Miglis, Mitchell G. (Frontiers in Neurology, 2022)
Background Autonomic dysfunction is a known complication of post-acute sequelae of SARS-CoV-2 (PASC)/long COVID, however prevalence and severity are unknown. Objective To assess the frequency, severity, and risk factors of autonomic dysfunction in PASC, and to determine whether severity of acute SARS-CoV-2 infection is associated with severity of autonomic dysfunction. Design Cross-sectional online survey of adults with PASC recruited through long COVID support groups between October 2020 and August 2021. Participants 2,413 adults ages 18–64 years with PASC including patients who had a confirmed positive test for COVID-19 (test-confirmed) and participants who were diagnosed with COVID-19 based on clinical symptoms alone. Main measures The main outcome measure was the Composite Autonomic Symptom 31 (COMPASS-31) total score, used to assess global autonomic dysfunction. Test-confirmed hospitalized vs. test-confirmed non-hospitalized participants were compared to determine if the severity of acute SARS-CoV-2 infection was associated with the severity autonomic dysfunction. Key results Sixty-six percent of PASC patients had a COMPASS-31 score >20, suggestive of moderate to severe autonomic dysfunction. COMPASS-31 scores did not differ between test-confirmed hospitalized and test-confirmed non-hospitalized participants [28.95 (15.62, 46.60) vs. 26.4 (13.75, 42.10); p = 0.06]. Conclusions Evidence of moderate to severe autonomic dysfunction was seen in 66% of PASC patients in our study, independent of hospitalization status, suggesting that autonomic dysfunction is highly prevalent in the PASC population and independent of the severity of acute COVID-19 illness.